Homeland. The complete fifth season [videorecording (DVD)] - Gansa, Alex (Twentieth Century Fox Home Entertainment, 2016)
Now working at a private security firm in Berlin, Carrie is trying to start a new life, but she soon discovers she can't escape her past. Blindsided by stunning betrayals, and without Saul and Quinn to rely on, Carrie must uncover a deadly conspiracy that puts thousands of lives at risk, including her own.